2016
DOI: 10.1017/s002221511600952x
|View full text |Cite
|
Sign up to set email alerts
|

A paired comparison analysis of third-party rater thyroidectomy scar preference

Abstract: Objective: To determine the length and position of a thyroidectomy scar that is cosmetically most appealing to naïve raters.Methods: Images of thyroidectomy scars were reproduced on male and female necks using digital imaging software. Surgical variables studied were scar position and length. Fifteen raters were presented with 56 scar pairings and asked to identify which was preferred cosmetically. Twenty duplicate pairings were included to assess rater reliability. Analysis of variance was used to determine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… 28 Furthermore, a study exploring third party rater preference for thyroidectomy scar noted that raters preferred low, short scars; as opposed to, longer thyroidectomy scars. 29 Interestingly, a recent study utilized a discrete choice experiment to evaluate the influence of cosmetic concerns on patients’ decision-making processes when choosing among different thyroidectomy approaches. They similarly concluded that presence of a neck scar also influenced patient decision-making, but this was dependent on patient age with younger patients preferring a scarless approach.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Furthermore, a study exploring third party rater preference for thyroidectomy scar noted that raters preferred low, short scars; as opposed to, longer thyroidectomy scars. 29 Interestingly, a recent study utilized a discrete choice experiment to evaluate the influence of cosmetic concerns on patients’ decision-making processes when choosing among different thyroidectomy approaches. They similarly concluded that presence of a neck scar also influenced patient decision-making, but this was dependent on patient age with younger patients preferring a scarless approach.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Chaung et al and Rajakumar et al evaluated patient's perception on the length, thickness or neck position of the thyroid scar. 3,28 This current study adds value by evaluating the patient's perception when presented with a neck scar versus a hidden scar at the axilla or hairline. This gives a direct comparison between SET versus conventional open thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there is an increasing variety of approaches available to patients, including remote access and 'scarless' in-the-neck surgery to achieve a satisfactory scar appearance post-surgery. 1,3 Open thyroid surgery was first described by Billroth and Kocher in the 1800s and is still the most established approach for thyroidectomy. 4 Despite the good operative outcomes of open thyroid surgery, new approaches are constantly created to overcome the concern of a visible scar over the neck made by the conventional Kocher incision.…”
Section: Introductionmentioning
confidence: 99%
“…There are some different methods of evaluating the quality of the scars [6][7][8] . They tend to be complex but are more complete when taking into account the opinion of the patients, and when the observation is made by someone other than the surgeon who performed the operation, which is an evident bias.…”
Section: /6mentioning
confidence: 99%